Development of a Data Analysis Module - Atharva Gupte; Kaushal Bhide; Swarupa Deshpande; Manas Apte; Rohan Rasane, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2023)
A module that gathers data from various sources like SQL databases or CSVs and then, with the help of this data, provides meaningful insights to the customer. The software will be an efficient way to track data from varied sources in real time. It will provide a centralized system to monitor and analyze the performance of any business/organization. With the help of this software, or dashboard an environment can be created for business analysis as well as management. This module includes all phases of the Data Analysis life cycle, like data collection, data pre-processing, data analysis, visualization, and eventually effective decision making. A holistic solution for each step is given by the software so as to yield as many insights as possible. In today’s time where data is the new currency, this software or module or dashboard will provide users with a wide range of options to work with and around data. With the help of this software, one can achieve effective monitoring and evaluation of the business sector. Due to the lack of such software, the available raw data is often not transformed and used for decision-making. To fill this void, this module will play a vital role. The software will provide customers with the options to check factors like tracking progress towards a set target, effective decision-making for planning, and predicting sector trends and performances. The customers will have autonomy to work with variable sizes and types of data. Propagating the results is also an important thing for the customers; therefore, the module or dashboard provides effective data visualization tools as well. Thus, this software is defined as an end-to-end solution for the customers.